Impact of digital knowledge on the adoption of digital marketing in the ron sejahtera women's farmer group, Cemani - Suryadi, Didik; Suprihatin, Dewi Nawang; Seto, Rehino Yanu; Pranata, Muhammad Fariz Yoga; Hantari, Dimar; Rizky, Anditya Gilang; Addilah, Aulia; Wijayanti, Bela Tri; Hidayati, Febry Nur (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Ron Sejahtera Women Farmers Group (KWT) is an activity in the smallest sphere of society that has fresh and processed agricultural products. These products are difficult to market using traditional methods, so the potential for using digital marketing is wide open. The adoption of digital marketing is important in order to be able to develop broader marketing. The adoption of digital marketing as a form of digital technology development is influenced by knowledge, perceptions of digital marketing, and daily consumer behavior. Methods: This research is an experimental research with 30 respondents located at KWT Ron Sejahtera in Cemani Village. The analysis method uses logit regression to determine the factors that influence the adoption of digital marketing and the t-test to assess the effectiveness of socialization as a form of knowledge addition about the adoption of digital marketing. Finding: The results show that knowledge has an important role in adopting digital marketing with socialization. Socialization significantly increases the knowledge of KWT Ron Sejahtera members. Other factors that influence the adoption of digital marketing in KWT Ron Sejahtera are knowledge about digital marketing, perception towards digital marketing, and participation as a member of KWT Ron Sejahtera. Conclusion: Increasing knowledge through socialization is important to be initiated by the government, private sector, and other stakeholders.